Civic Engagement and the Athenian Jury - Lanni, Adriaan (Classica et Mediaevalia, 2026)
Why did hundreds of Athenians show up for jury duty, even though the vote of any one juror was unlikely to affect the outcome of a verdict issued by a 201- or 501-person jury? This paper draws on the extensive political science literature addressing an analogous modern problem – the paradox of voter turnout – to suggest a framework for approaching this puzzle. The modern theoretical and empirical literature suggests several possible factors to explain why people vote, including material incentives, social incentives, a sense of civic duty, and the expressive benefits of voting. This literature tends to focus on a robust sense of civic duty and expressive voting as the primary reasons for modern voter turnout. I argue that expressive voting was likely the most important motivating factor for ancient Athenian jurors, but that the expressive benefits of judging in Athens were specific to the Athenian context. Serving as a juror gave ordinary Athenians the satisfaction of being able to express a judgment about the behavior of wealthy citizens and to make moral judgements about public norms.